Dynamic capabilities - what do we 'actually' know? : a systematic assessment of the field and a research agenda - Giudici, Alessandro (Cranfield University, 2009)
How organizations deal and manage strategic change is a fundamental problem in management studies. An important way increasingly chosen to implement strategies is through programmes. Programme Management is an emerging discipline that aims to research how programmes could be more effective in delivering their expected strategic benefits. In order to obtain this, it is recognised that successful programmes require a continuous development of capabilities at different levels and on a context-dependent basis. My research project aims to use the theoretical lens of dynamic capabilities to explore how different capabilities could be integrated, built, and reconfigured in a context of Programme Management. In order to establish robust bases for the PhD, this thesis presents a systematic literature review (and its formal protocol) of the dynamic capabilities view of the firm. In doing so, in this MRes thesis I test for the level of reification of the concept of dynamic capabilities and highlight some major theoretical challenges. I observe that the field is currently affected by a conversational misalignment that is hindering the potential for further research. In particular, the argument is that empirical and conceptual developments have grown from the same foundations but with low mutual influence. In addition, I utilize content and thematic analysis to explore areas where future efforts may be fruitfully directed. Overall, findings show how dynamic capabilities are an emerging field where several research gaps may be identified. However, they also highlight how it is fundamental to clarify on which theoretical foundations any research builds. Finally, I introduce some interesting findings that may be of help for an operationalization in a Programme Management context. In particular, I suggest that a high-potential and unexplored theme is how dynamic capabilities are created and sustained in the inter-organizational relationship between business service providers and their client firms.